Anesthetics disrupt brain development via actions on the mTOR pathway - Xu, Jing (Commun Integr Biol, 2018)
Experiments conducted in non-human primates have recently provided new evidence supporting a longstanding concern that exposure to general anesthesia during late intrauterine life or early childhood can cause lasting cognitive deficits through harmful effects on brain development. The mammalian target of rapamycin (mTOR) signaling system plays a key role in both normal brain development and in a wide range of developmental disorders that are characterized by cognitive deficits. Intriguingly, our recently published work shows that anesthetics can chronically alter mTOR signaling in the hippocampal dentate gyrus and that normalization of mTOR signaling can prevent anesthesia-induced perturbation of structure and function. In this addendum, we briefly discuss the putative role of mTOR in developmental anesthetic neurotoxicity.